Fetal origins and parental responses - Douglas Almond; Bhashkar Mazumder (Federal Reserve Bank of Chicago, 2012)
We review the literature on how parental investments respond to health endowments at birth. Recent studies have combined insights from an earlier theoretical literature on how households allocate resources within the family, with a growing empirical literature that identifies early life health shocks using sharp research designs. We describe the econometric challenges in identifying the behavioral responses of parents and how recent studies have sought to address these challenges. We also discuss the emerging literature that has considered how there may be dynamic complementarities in parental investments due to the developmental nature of human capital production and how there may be multiple dimensions of skill. We find that thus far, the bulk of the empirical evidence is consistent with notion that parents reinforce initial endowments.
Keywords: 330